The Mediation (Emotional Self-Control) and Moderation (Fun) of the Relationship Between Receiving and Perpetrating Hate Speech Among Boys and Girls in Almeria (Spain) - Francisco Villegas Lirola; Pilar Rodriguez Martinez (Social Sciences)
This article presents an analysis of the mediation and moderation of the suffering and perpetration of hate speech among adolescents in Almería (Spain), taking into account gender differences. For this purpose, data from a questionnaire completed by secondary school students (N = 535) in four schools in Almería (Spain) was analyzed. For the analysis, an index of emotional self-control was constructed and introduced as a mediator between receiving hate speech and perpetrating it. In addition, the moderating role of revenge and fun motives in this relationship was analyzed, finding that the revenge motive is not significant and the fun motive is significant (for boys). The results suggest that receiving hate speech does not mean that one commits hate speech. It occurs when there is a low level of self-control and increases (for boys) when hate speech is perceived as fun. Therefore, we can say that for both boys and girls, it is necessary to improve emotional self-control. In addition, toxic masculinity is related to low emotional self-control, but is loaded with the view that hate speech is funny.